2009
DOI: 10.2337/dc08-1736
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Improves Endothelial Dysfunction in Statin-Treated Type 2 Diabetic Patients

Abstract: OBJECTIVE -The vascular benefits of statins might be attenuated by inhibition of coenzyme Q 10 (CoQ 10 ) synthesis. We investigated whether oral CoQ 10 supplementation improves endothelial dysfunction in statin-treated type 2 diabetic patients.RESEARCH DESIGN AND METHODS -In a double-blind crossover study, 23 statintreated type 2 diabetic patients with LDL cholesterol Ͻ2.5mmol/l and endothelial dysfunction (brachial artery flow-mediated dilatation [FMD] Ͻ5.5%) were randomized to oral CoQ 10 (200 mg/day) or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 15 publications
(20 reference statements)
0
84
0
8
Order By: Relevance
“…19 Supplementation with CoQ10 (200 mg/day for 3 months) in type 2 diabetics significantly improved endothelial dysfunction, quantified via brachial artery flow-mediated dilation, translating as a 10-20% reduction in residual cardiovascular risk. 20 Hosseinzadeh-Attar et al 13 found CoQ10 supplementation (200 mg/day for 3 months) significantly reduced circulatory levels of asymmetric dimethylarginine, a marker of endothelial dysfunction and cardiovascular event risk factor. In the Q-SYMBIO study (a randomised double-blind multicentre trial of CoQ10 as adjunctive treatment of chronic heart failure with focus on SYMptoms, BIOmarker status and long-term outcome), supplementation with CoQ10 (300 mg/day for 2 years) improved heart function and reduced cardiovascular-related mortality by 43% in heart failure patients, 10% of whom had type 2 diabetes.…”
Section: Effect Of Coq10 Supplementation On Vascular Dysfunctionmentioning
confidence: 99%
“…19 Supplementation with CoQ10 (200 mg/day for 3 months) in type 2 diabetics significantly improved endothelial dysfunction, quantified via brachial artery flow-mediated dilation, translating as a 10-20% reduction in residual cardiovascular risk. 20 Hosseinzadeh-Attar et al 13 found CoQ10 supplementation (200 mg/day for 3 months) significantly reduced circulatory levels of asymmetric dimethylarginine, a marker of endothelial dysfunction and cardiovascular event risk factor. In the Q-SYMBIO study (a randomised double-blind multicentre trial of CoQ10 as adjunctive treatment of chronic heart failure with focus on SYMptoms, BIOmarker status and long-term outcome), supplementation with CoQ10 (300 mg/day for 2 years) improved heart function and reduced cardiovascular-related mortality by 43% in heart failure patients, 10% of whom had type 2 diabetes.…”
Section: Effect Of Coq10 Supplementation On Vascular Dysfunctionmentioning
confidence: 99%
“…Given the potential for statins to inhibit the cellular synthesis of plasma CoQ 10 , a by-product of isoprenoid metabolism, their full benefit on improving endothelial function may be blunted [232,233]. In a randomized, double-blind, crossover study, CoQ 10 supplementation significantly improved brachial artery FMD in statin-treated T2D patients with LDLcholesterol <2.5mmol/l and ED [234]. In patients with CAD (20% with diabetes and 80% statin-treated), CoQ 10 supplementation improved ecSOD levels and brachial artery FMD, indicating that the beneficial effects of CoQ 10 on endothelial function are in part related to improvements in local vascular oxidative stress [235].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Specifically, twelve weeks of supplementation with 200mg of CoQ 10 or placebo resulted in significant increases in plasma CoQ 10, respectively, and improved flow mediated dilation (S. J. Hamilton et al, 2009;Watts et al, 2002). However, neither trial found an alteration in biomarkers of oxidative stress or antioxidant capacity, lipid profiles, glycemic control, or blood pressure after supplementation.…”
Section: Coenzyme Q 10mentioning
confidence: 99%